Caracterização nutricional do mesocarpo de babaçu (Orbignya phalerata Mart.) nos municípios de Arari, Esperantinopólis e Pinheiro - MA - Leite, Ana Maria Maciel (2003)
The mesocarp of the babassu firuit (Orbignya ssp) it is historically taken advantage by the traditional populations. This work tried to do a nutritional characterization of the flour of the babassu mesocarp, tends as objectives to analyze the carbohydrate tenors, lipids, proteins, fibers, humidity, ashes and minerais (Ca, Mg, Na, K, Cu, Zn, Fe, Mn). Bromatologics analyses were accomplished for comparison effect among samples of three different marks of mesocarp flours marketed in the State of Maranhão (Brazil), being 20 samples of each marks in a total of 60 samples. The analyses were in two períods. At each periods were analysed 30 samples, 10 samples of each marks at a even lot, comíng of the municipal districts of Arari, Esperantinópolis and Pinheiro, where it was determined the centesimal composition of these constituent ones. The Chemical analyses followed the manual of norms and techniques of the Instituto Adolfo Lutz of São Paulo. The médium values found with limit of trust of 95% of probability for the carbohydrate tenors, starch, lipids, proteins, fibers, humidity and ashes, they are respectively: in the samples of Arari: (80,75g% ± 3,00 and 87,34g% ± 3,50), (72,67g% ± 1,68 and 75,20g% ± 1,80), (1,82g% ± 0,03 and 1,80g% ± 0,03), (1,88g% ± 0 ,1 0 and 2,75g% ± 0,15), (0,75g% ± 0,03 and 0,80g% ± 0,02), (15,8g% ± 0,70 and 7,80g% ± 0,50), (0,38g% ± 0,01 and 0,31 g% ± 0,01); Esperantinópolis: (81,60g% ± 3,04 and 84,55g% ± 3,25), (73,44g% ± 1,78 and 72,50g% ±1,65), (2,04g% ± 0,05 and 2,10g% ± 0,04), (2,28g% ± 0,12 and 1,95g% ± 0,10), (0,70g% ± 0,02 and 0,70g% ± 0,01), (16,02g% ± 0,90 and 10,95g% ± 0,60), (1,02g% ± 0,03 and 1,45g% ± 0,02), Pinheiro: (81,01g% ± 3,00 and 82,00g% ± 3,05), (72,91 g% ± 1,90 and 70,10g% ±1,70), (1,98g% ± 0,03 and 1,90g% ± 0,02), (2,46g% ± 0,02 and 2,50g% ± 0,02), (0,65g% ± 0,07 and 0,63g% ±0,02), (16,80g% ± 0,95 and 13,35g% ±0,70), (0,22g% ± 0,01 and 0,25g% ±0,01). With the results \obtained observance different variationes a due to the factorial climatics, ambients and to estorem entThe method used for quantification of the minerais was the spectrofotometry of atomic absorption with fires. The tenors of calcium, magnesium, sodium, potassium, copper, zinc, iron and manganese are respectively: in the samples of Arari: 20mg%, 40mg%, 0,21%, 65mg%, 0,33mg%, 0,02mg%, 1,84%, 0,13mg%; in the samples of Esperantinópolis: 26mg%, 40mg%, 0,39mg%, 114mg%, 0,45mg%, 0,08mg%, 2,5mg%, 0,14mg%; in Pinheiro's sample: 25mg%, 47mg%, 0,52mg%, 91mg%, 0,22mg%, 0,17mg%, 2,4mg%, 0,13mg%. The data of thís work show that the flours of studíed mesocarp are good sources in the researched nutrients, possessíng superior concentrations or at least equivalent to the traditional sources